Evaluasi Pelaksanaan Pembelajaran di Pendidikan Anak Usia Dini Wira Putra - Wiratama, Dhika; Setyaningsih, Setyaningsih; Sukodoyo, Sukodoyo (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2018)
Abstract The school research is based on the fact that evaluation has not been done Wira Putra nursery school. This study attemps to describe and provide recommendations on the presentation of teaching at Wira Putra nursery school. The research is a evaluative research with a qualitative approach and a quantitative approach. The data were collected through observation , interview, and documentation. The observation was conducted by direct observation. The interview was conducted in depth with the informants. Documentation was conducted by way of photographing an image which could be made by experimental evidence. In addition, the researcher also took the data that were related to the still research context, input, process, and product (CIPP). The validity of data were measured by extension involvement, an increase in diligence and tenacity, triangulation, member check. The data analysis related CIPP use the model analysis of Miles and Huberman. The evaluation of the implementation of learning is as follows: (1) The context has component parts of policy formation of Wira Putra nursery school based on the distribution of adequate access to nursery school, increasing the quality of relevance and competitiveness of nursery school, and the increase in good govermance; inclassical component of the learning environment adapted to the students; cooperate with students, parents. Dharma Syailendra Education Foundation, Syailendra Buddhist College, comparative study to another nursery school; (2) The input of active and curios characteristic of students; characteristic of teachers who educate and nurture with affection without discriminating students, educator who know the development of students management; characteristic provide access to services as the standard quality of nursery school; (3) The process of the implementation of the learning went very well; external factors which support the learning activities were public trust of Thekelan hamlet, the institutions provided excellent service; the internal distribution of venues being used for rolling when learning took place, the difference of preference in material that students have a tendency to like certain material, and the different mood students as the effects from home and; (4) The product is in the form the achievement of the level of development of school tuition including a moral issue and religious values, motoric (rough motoric and soft motoric) skill, cognitive, language, art, social and emotional values. Abstrak Penelitian ini bertujuan untuk mendeskripsikan dan memberikan rekomendasi pelaksanaan pembelajaran di PAUD Wira Putra. Penelitian ini merupakan penelitian evaluatif dengan pendekatan kualitatif dan kuantitatif. Teknik dan instrumen pengumpulan data melalui observasi, wawancara, dan dokumentasi untuk mengambil data context, input, process, dan product (CIPP). Keabsahan data diukur dengan perpanjangan keterlibatan, peningkatan ketekunan dan kegigihan, triangulasi, member check. Analisis data terkait CIPP menggunakan model analisis dari Miles dan Huberman. Hasil evaluasi pelaksanaan pembelajaran sebagai berikut: (1) Context memiliki komponen kebijakan pembentukan PAUD Wira Putra berlandaskan peningkatan pemerataan akses layanan PAUD, peningkatan mutu relevansi dan daya saing PAUD, dan peningkatan good govermance; komponen penciptaan lingkungan pembelajaran individual; menjalin kerja sama dengan orang tua peserta didik, Yayasan Pendidikan Dharma Syailendra, Sekolah Tinggi Agama Buddha Syailendra, studi banding ke PAUD lain; (2) Input berupa karakteristik peserta didik yang aktif dan memiliki rasa ingin tahu tinggi; karakteristik pendidik mengasuh dengan kasih sayang tanpa membedakan peserta didik, pendidik mengetahui aspek perkembangan peserta didik; karakteristik pengelola memberikan akses layanan yang bermutu sesuai standar PAUD; (3) Process pelaksanaan program pembelajaran berlangsung sangat baik; faktor penunjang eksternal kegiatan pembelajaran berupa kepercayaan masyarakat dusun Thekelan, pihak lembaga memberikan pelayanan sangat baik; faktor penghambat internal keterbatasan tempat yang digunakan untuk rolling saat pembelajaran berlangsung, perbedaan rasa suka terhadap materi sehingga peserta didik memiliki kecenderungan memilih materi yang hanya disuka, dan perbedaan mood peserta didik dikarenakan pengaruh dari rumah; dan (4) Product berupa hasil pencapaian tingkat perkembangan peserta didik mencakup aspek moral dan nilai-nilai agama, motorik , kognitif, bahasa, seni, dan sosial emosional.